1989
DOI: 10.1104/pp.89.1.138
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Biosynthesis-Inducing Protein from Cellulysin Is an Endoxylanase

Abstract: The proteinaceous ethylene biosynthesis-inducing factor (EIF) that was purified from Cellulysin was also shown to contain a xylanase activity. In all nondenaturing protein separation methods employed (Sephacryl S-200 chromatography, and preparafive isoelectric focusing and agarose electrophoresis), xylanase ac-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 24 publications
(27 reference statements)
2
54
0
2
Order By: Relevance
“…Because many of these chemicals (except salicylic acid) trigger ethylene biosynthesis, chemical elicitation of PR protein accumulation may be via ethylene. Recently, an endoxylanase has been purified from culture filtrates of Trichoderma viride and has been identified as the ethylene-inducing factor in Cellulysin (a commercial cellulase-containing product) (13). Here we show that this enzyme induces synthesis of PR proteins when applied directly to tobacco leaves.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Because many of these chemicals (except salicylic acid) trigger ethylene biosynthesis, chemical elicitation of PR protein accumulation may be via ethylene. Recently, an endoxylanase has been purified from culture filtrates of Trichoderma viride and has been identified as the ethylene-inducing factor in Cellulysin (a commercial cellulase-containing product) (13). Here we show that this enzyme induces synthesis of PR proteins when applied directly to tobacco leaves.…”
mentioning
confidence: 74%
“…Experiments involving ethylene evolution have been carried out on leaf discs (6,13). We wished to confirm the biosynthesis ofethylene and its inhibition in our experimental system, i.e.…”
Section: -Ethylene-and Non-ethylene-dependent Pathways In Pr-pq Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The 22-kD fungal protein ethylene-inducing xylanase (EIX; Fuchs et al, 1989) induces ethylene biosynthesis, electrolyte leakage, pathogensis-related protein expression, and HR in specific plant species and/or varieties (Bailey et al, 1990(Bailey et al, , 1993Ron et al, 2000;Elbaz et al, 2002). Analysis of EIX mutants lacking enzymatic activity (b-1-4-endoxylanase) but retaining elicitation activity showed that the xylanase activity is not required for the HR elicitation process because the protein per se functions as the elicitor (Enkerli et al, 1999;FurmanMatarasso et al, 1999;Rotblat et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme apparently degrades P-1,4-xylan linkages in the plant cell wall and is an exceptionally potent inducer of chitinase accumulation. It also promotes ethylene evolution (Fuchs et al, 1989); nevertheless, ethylene is not required in its mode of action (Lotan and Fluhr, 1990b).…”
Section: Introductionmentioning
confidence: 99%